Chronic adult T-cell Leukemia in a young male after blood transfusion as a newborn - Colucci, Magalí (2016)
Human T-cell Lymphotropic virus type 1 (HTLV-1) is the etiological agent of Adult T-cell Leukemia/Lymphoma (ATLL) and HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis (HTM/TSP). Areas of extremely high HTLV-1 prevalence are surrounded by areas of middle or very low prevalence. ATLL is an aggressive lymphoproliferative malignancy of peripheral T cells, with an incidence of less than 5% in HTLV-1-infected individuals. ATLL develops in the majority of cases in individuals who were infected with HTLV-1 by their mothers due to prolonged breastfeeding. In non-endemic areas, ATLL is usually limited to immigrants from endemic regions. Very few cases of ATLL have been diagnosed in recipient patients few years after an organ transplantation or blood transfusion worldwide. Achieving an accurate and fast diagnosis of ATLL can be challenging due to the lack of professional experience, delayed consultation and difficulty in its subclassification. We present a case of a delayed onset of a chronic ATLL in an 18-years-old male that was transfused with blood components as a premature newborn in Buenos Aires, a non-endemic city of South America.